Fractional Diffusion Equations with Internal Degrees of Freedom (Journal of Computational Mathematics, 2003)
We present a generalization of the linear one-dimensional diffusion equation by combining the fractional derivatives and the internal degrees of freedom. The solutions are constructed from those of the scalar fractional diffusion equation. We analyze the interpolation between the standard diffusion and wave equations defined by the fractional derivatives. Our main result is that we can define a diffusion process depending on the internal degrees of freedom associated to the system.
Keywords: Fractional derivative; Diffunors; Diffusion process; Generalized Dirac equation.